A review of laboratory-acquired infections in the Asia-Pacific: understanding risk and the need for improved biosafety for veterinary and zoonotic diseases - Siengsanan-Lamont, J; Blacksell, SD (MDPI, 2018)
A rapid review was performed to determine (1) the number and causes of reported laboratory-acquired infections (LAI) in the Asia-Pacific region; (2) their significance and threat to the community; (3) the primary risk factors associated with LAIs; (4) the consequences in the event of a LAI or pathogen escape; and (5) to make general recommendations regarding biosafety practices for diagnosis and research in the Asia-Pacific region. A search for LAI and zoonoses in the Asia-Pacific region using online search engines revealed a relatively low number of reports. Only 27 LAI reports were published between 1982 and 2016. The most common pathogens associated with LAIs were dengue virus, Arthroderma spp., Brucella spp., Mycobacterium spp., Rickettsia spp., and Shigella spp. Seventy-eight percent (21 out of 27 LAI reports) occurred in high-income countries (i.e., Australia, Japan, South Korea, Singapore, and Taiwan) where laboratories were likely to comply with international biosafety standards. Two upper-middle income countries (China (2), and Malaysia (2)) and one lower-middle income country (India (2)) reported LAI incidents. The majority of the reports (fifty-two percent (14/27)) of LAIs occurred in research laboratories. Five LAI reports were from clinical or diagnostic laboratories that are considered at the frontier for zoonotic disease detection. Governments and laboratories in the Asia-Pacific region should be encouraged to report LAI cases as it provides a useful tool to monitor unintended release of zoonotic pathogens and to further improve laboratory biosafety. Non-reporting of LAI events could pose a risk of disease transmission from infected laboratory staff to communities and the environment. The international community has an important and continuing role to play in supporting laboratories in the Asia-Pacific region to ensure that they maintain the safe working environment for the staff and their families, and the wider community